Macrophage Chemoattractant Protein-1 Deficiency Fails to Restrain Macrophage Infiltration Into Adipose Tissue - KIRK, Elizabeth A; SAGAWA, Zachary K; MCDONALD, Thomas O; O'BRIEN, Kevin D; HEINECKE, Jay W (Diabetes (New York, N.Y.), 2008)
OBJECTIVE--Monocyte chemoattractant protein-1 (MCP-1), a CC-motif chemokine, has been proposed to play critical roles in insulin resistance and recruitment of monocytes into adipose tissue. We hypothesized that the absence of MCP-1 would improve the former and diminish the latter. RESEARCH DESIGN AND METHODS--We investigated these two hypotheses by quantifying glucose metabolism and the accumulation of macrophages in adipose tissue of control and MCP-1-deficient ([Mcp1.sup.-/-]) mice after feeding the animals a high-fat diet for 10 or 16 weeks. RESULTS--We first established that the two strains were in the same genetic background and that macrophage recruitment into inflamed peritoneum was markedly reduced in the MCP-1-deficient animals. In striking contrast, independent studies at two different facilities at either an early or late time point failed to detect any impairment in macrophage accumulation in adipose tissue of fat-fed [Mcp1.sup.-/-] mice. Immunoblot analysis revealed higher levels of Mac2, a macrophage-specific protein, in multiple fat depots of [Mcp1.sup.-/-] mice fed a high-fat diet. These mice also had significantly more adipose tissue than control mice, but their glucose metabolism was similar. CONCLUSIONS--Our observations suggest that MCP-1 does not play a prominent a role in promoting macrophage recruitment into adipose tissue or in systemic insulin resistance.